INTRODUCTION OF COMPUTER TECHNOLOGY IN EDUCATION - Khamrakulov Abdurakhmat Karimovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article discusses the possibilities of using computer programs in teaching graphic disciplines. It is argued that the interest of students in the science of engineering graphics has increased due to the use of computer programs.